Inequalities in utility and leisure cycling in England, and variation by local cycling prevalence. (July 2018) - Goodman, Anna; Aldred, Rachel
Highlights: Cycling in England is unequal by gender, age, disability and ethnicity. Local authorities with more cycling see less age and gender inequality. More educated people are more likely to ride for recreation. Car owners are less likely to cycle for utility, but more likely to cycle for recreation. Many inequalities are absent or lower in higher-cycling countries or authorities. Abstract: This paper analyses Active People Survey data (collected 2011/12 to 2015/16) on 789, 196 English adults, providing new information on how a range of socio-demographic factors are associated with utility and leisure cycling. Substantial inequalities are found in relation to gender, age, disability, and ethnicity for both types of cycling. For gender and age, and perhaps for disability in relation to recreational cycling, inequalities are moderated by local cycling prevalence such that English authorities with more cycling see less inequality. For education and car ownership, the picture is more mixed. Individuals with higher educational levels are more likely to participate in leisure cycling, but within most English local authorities this association is absent for utility cycling. Car ownership is negatively associated with utility cycling, but positively associated with recreational cycling. The paper's discussion section puts these inequalities in context, and discusses the significance of the fact that some inequalities seem to be less pronounced or even absent in some contexts. It is argued that more research and a broader conceptualisation of cycling inequalities are needed to better understand and address inequalities in cycling participation.